Migration and development in EU countries comparative analysis of approaches and projects - Nováková, Michaela (2013)
The dissertation is focusing on migration in the EU, specifically on comparing Vietnamese communities in the Czech Republic and in France. The first and the second part of the dissertation is comparing these two Vietnamese communities. The historical background, migrants'integration to local community and position of immigrants at the Czech and French labour markets. The third part is assessing the impact of these communities on Vietnam.